Epic Narratives in the Hoysaḷa Temples : The Rāmāyaṇa, Mahābhārata and Bhāgavata Purāṇa in Haḷebīd, Belūr and Amṛtapura - Evans, Kirsti. (Numen Book Series, 1997)
This volume is a detailed exposition of the visual retellings from the Rāmāyaṇa, Mahābhārata and Bhāgavata Purāṇa on specific South Indian Hoysaḷa temples. The first part of the book deals with the Amṛteśvara temple, particularly its narrative panels depicting the Rāmāyaṇa, Mahābhārata and Bhāgavata Purāṇa. The text is a résumé of episodes paired with photographs which illustrate and review the visual retellings and explore Indian techniques of visual narrative. Corollary material from other Hoysaḷa temples with narrative reliefs, including new sites, is presented in the second part. There are very few published contextual studies of Indian narrative sculptures, and so the book is a contribution to the documentation of Indian medieval art, examining visual narratives within the context of the Hindu temple. The book is illustrated with 150 photographs.